PENGUATAN UMKM DAN LITERASI KEUANGAN SYARIAH DI PEDESAAN DI DESA CURUG BITUNG, KECAMATAN NANGGUNG, KABUPATEN BOGOR: PENGUATAN UMKM DAN LITERASI KEUANGAN SYARIAH DI PEDESAAN DI DESA CURUG BITUNG, KECAMATAN NANGGUNG, KABUPATEN BOGOR - Susi Melinasari; Dewi Purwati; Keris Kartono (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Curug Bitung Village play a vital role but experience stagnation due to low financial and managerial literacy, as well as vulnerability to exploitative financial practices such as illegal online loans and loan sharks. This community service program aims to provide integrated education on Sharia Financial Literacy so that MSME actors can avoid MAGHRIB practices (Maysir, Gharar, Riba). The method used is Participatory Action Research (PAR), which actively involves the community through five stages: social mapping, focus group discussions (FGD), action planning, workshop implementation, and evaluation. The results show that the majority of micro-scale MSMEs successfully classified their businesses, deconstructed misconceptions about daily transactions, and practiced simple cash flow management using a Pocket Cash Book to separate personal and business finances. In addition, there was a transformation in the residents' financial attitudes in controlling consumptive behavior by distinguishing needs and wants based on theological-spiritual values. In conclusion, this integrated educational intervention successfully equipped residents with sound managerial skills and a strong ideological fortress to advance rural MSMEs.